Feeding whole grain with pelleted diets to growing broiler chickens - Kiiskinen, Tuomo (Agricultural and Food Science, 1996)
In three trials with growing broilers (aged 12-8 days) the proportion of whole grain (WG) was increased step by step up to 30% (Trial 1) along with commercial starter (S) and grower (G) pellets or up to 40% (Trial 2) and 50% (Trial 3) with special balancer (BA) pellets (crude protein 250 g/kg). WG accounted for about 20%, 31% and 38% of the broilers’ total feed intakes, respectively. In Trial 1, the grain was exclusively wheat (W). In the other trials, also mixtures of wheat and barley (W:B 70:30, 50:50) were used. Crude protein analyses of feed remains revealed that birds did not to any considerable extent select between pellets and grain. Mixing wheat with S or G pellets reduced feed intake significantly (P<0.05) and, as a consequence, the growth rate decreased by 3-5%. However, the feed efficiency (FCR) of the SW birds was significantly (P<0.05) better than that of the control and GW birds. In Trial 2, the BAWG treatments reduced feed intake (P<0.05) and weight gain, but there were no significant differences in FCR. In Trial 3, the growth rate was similar with all the regimens, and birds fed the BAW diet consumed feed less (P<0.001) but more efficiently (P<0.001) than those fed the other diets. In each trial, the WG feedings increased markedly (50-90%) the empty gizzard weight. Fatness of broilers decreased significantly (P<0.05) when whole wheat was fed with the S diet (Trial 1) but not so when fed with the BA diet (Trials 2 and 3). The present results suggest that during the growing phase, broiler chickens can be fed efficiently with mixtures of a pelleted starter or a pelleted balancer diet and whole wheat which can partly be replaced by barley.